**Ask Dr. Math Equation of a Line in 3-D Space Math Forum**

NOTE: y = (-ax + c)/b is the same thing as y = (c - ax)/b. We can apply the commutative rule of addition on the numerator allowing us to switch the terms around not changing the value of the entire fraction.... 15/05/2011 · No idea why they do it, but one good reason to write it that way is because there's no "privileged" coordinate in a plane. Think about the equation for a circle -- it only gets confusing when you try to define y as a "function" of x or vice-versa.

**how to convert ax+by=c to a y=mx+b? example. 2x+5y=10**

Earlier in this chapter we have expressed linear equations using the standard form Ax + By = C. Now we're going to show another way of expressing linear equations by using the slope-intercept form y = mx …... Many linear equations are given in slope-intercept form (y = mx + b), and sometimes they must be converted to standard form (Ax + By = C). Converting slope-intercept to standard form is mostly a matter of converting fractions to integers and can be done on paper in a couple minutes.

**Ask Dr. Math Equation of a Line in 3-D Space Math Forum**

Question 316872: Write the standard form (ax+by=c) of the equation of the line with the following conditions. 1. Through: (1,2) Slope; 7 What i have tried: i have tried to graph it. i used the slope. how to much to set up laundry coin business 13/01/2012 · I assume you mean the linear formula y=mx+b. Okay, well if you begin with an equation such as 4y-2x=10, you need to solve for "y=" In order to get y=, you must move the other things to the other side of the equation.

**Coordinate geometry y=mx +c convert to general form ax+by**

Equation of a Plane. A plane in 3-space has the equation . ax + by + cz = d, where at least one of the numbers a, b, c must be nonzero. As for the line, if the equation is multiplied by any nonzero constant k to get the equation kax + kby + kcz = kd, the plane of solutions is the same. how to write a school captain speech wikihow 4/04/2009 · for ax+by=-c it would be 2x + -1y = 1 so c can equal -1 (becuase of the negative out front of the c) or -2x + 1y=-1 so c can equal 1 but the correct standard form is when the function = 0. you will see why when you do more advanced maths.

## How long can it take?

### Factor polynomials on the form of ax^2 + bx +c Mathplanet

- When graphing an equation of the form y=mx+c how do you
- Exploring Parabolas y = ax^2 + bx + c University of Georgia
- Converting to slope-intercept form (video) Khan Academy
- Equation of a straight line point-slope intercept two

## How To Write Y Mx C In Ax By C

Farzana I was wondering if you could please explain to me how I would write the equation of line through the given points [(-3,7), (0,5)] in Ax+By=C form.

- To get it more clear let us compare the equation ax + by = λ with equation ax + by + c = 0. It follows that to write the equation of a line parallel to a given straight line we simply need to replace the given constant by an arbitrary constant, the terms with x and y remain unaltered. For example, the equation of a straight line parallel to the straight line 7x - 5y + 9 = 0 is 7x - 5y + λ
- I know how to write the line in slopeintercept form I know how to write the line in standard form . Day 2 Different Forms of the Equation of a Line.notebook 3 March 24, 2015 We can write the equation of a line in many different forms: y = mx + b Ax + By + C = 0 Ax + By = C. Day 2 Different Forms of the Equation of a Line.notebook 4 March 24, 2015 SlopeIntercept Formy = mx + b
- 16/03/2008 · How to rearrange y=mx+c to ax+by+c=0? I been working with an equation -x+3=y I thought that by subtracting y from both sides i could end up with -x+3-y=0 though that doesn't work and I am not sure why, its been a while since i did this stuff.
- -Ax + y=C (same as… -mx+y=b)-(-Ax+y=C) ê Ax-y=-C ¨ If your original slope (m) is a fraction: ¶ follow the steps above (move mx to opposite side and . get rid of negative if needed): y= -mx+b ê mx+y=b. y= mx+b ê-mx+y=b ê mx-y=-b · Now get rid of the fraction by multiplying each number . by the fraction’s denominator: (3/4)x+y=2 ê 4(3/4x+y=2) ê 3x+4y=8 ¨ Now here are a couple of